The impact of social capital on consumers' engagement in EWOM and their purchase intentions - Baykal, Bilge. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
Consumers often seek recommendations before they make a commitment to purchase. Social networks are one of the most appropriate communication platforms on which they can ask other consumers' opinions about various topics. In the literature, the social capital concept is discussed to play a vital role in the process of WOM transmission but no integrated theoretical model or empirical study exists that fully defines and analyzes the relationships between social capital, eWOM and the purchase intentions of consumers on social network site context. This dissertation attempts to fill this gap by proposing and testing a holistic theoretical model which aims to determine the impact of social capital dimensions on eWOM and purchase intentions of consumers through an extensive literature review, a series of exploratory qualitative studies and a large-scale survey-based quantitative study of data collected from 980 users of social media specifically, namely Facebook, Twitter and Instagram, and provides support for the reliability and validity of the proposed model. The findings demonstrate that there exists a direct relationship between the dimensions of social capital, consumers' engagement in eWOM and purchase intentions, but the strength of relationships varies. Among these dimensions, social network culture emerges as having the strongest effect on consumers' engagement in eWOM, followed by tie strength and interpersonal trust. Two moderators-gender and social network site usage intensity-are identified as influences of the relationships between model constructs. The implications for marketing theory and practice and directions for future research are discussed in the conclusion part of the study.
Keywords: Social capital (Sociology); Online social networks.; Consumers -- Attitudes.